The youth triathlete - Bergeron, F. M. (Triathlon Medicine, 2019)
Triathlon training and participation during youth can indeed be an attractive variable physical activity and diverse sport solution for encouraging health, fitness, psychosocial and character development, and academic and life success. But this can only be achieved if the underlying paradigm for the youth triathlete is underpinned by healthy and sustainable participation with sensible progressive development that is youth centered. Closely matching individual physical, athletic, and psychosocial/emotional development to the progressive demands and expectations of the sport is essential. This is, however, notably difficult for a youth athlete, owing to a constantly and uniquely changing base that is highly affected by normal physical growth, biological maturation, behavioral development, and their interactions. The model must also be individualized and promptly responsive to a young athlete's changing needs, goals, and early stages of evolving problems. For the youth triathlete, the sport experience and success (however defined) will always evolve on an individual trajectory along an unpredictable continuum. And coaches, parents, and young athletes should appreciate that early achievement or struggle as a youth triathlete is not always predictive of continued engagement or future performance, achievement, or enjoyment in the sport.